2017
DOI: 10.1002/hep4.1054
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic steatofibrosis independently predicts mortality in nonalcoholic fatty liver disease

Abstract: Nonalcoholic steatohepatitis (NASH) is the progressive form of nonalcoholic fatty liver disease (NAFLD). The minimal pathologic criteria for NASH include hepatic steatosis, ballooning degeneration, and lobular inflammation. The resolution of NASH, which relies on the loss of ballooning degeneration, is subject to sampling and observer variability in pathologic interpretation. Ballooning is associated with advanced hepatic fibrosis in cross‐sectional studies but is not a predictor of mortality in NAFLD. Fibrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
117
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 32 publications
3
117
0
Order By: Relevance
“…The annual transition probabilities for the all NASH model are shown in Table . Transition probabilities were derived for each health state from clinical trials, systematic literature reviews, meta‐analyses, and our previously published model . The transition probabilities for F1, F2, F3, and CC to later stages of liver disease were obtained from a recent meta‐analysis .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual transition probabilities for the all NASH model are shown in Table . Transition probabilities were derived for each health state from clinical trials, systematic literature reviews, meta‐analyses, and our previously published model . The transition probabilities for F1, F2, F3, and CC to later stages of liver disease were obtained from a recent meta‐analysis .…”
Section: Methodsmentioning
confidence: 99%
“…In this context, there are a number of studies that have suggested that subjects with histologic NASH are at risk for progressive liver disease and that those with significant fibrosis are at the greatest risk . In fact, the stage of fibrosis has been shown to be the only and most reliable predictor of liver‐related mortality . Therefore, one can argue that these are the patients with the most urgent need for treatment.…”
mentioning
confidence: 99%
“…In a separate Markov model focusing on NASH and advanced NASH in the United States, investigators determined that in 2017 there were 5,527,812 adult subjects with NASH (18‐79 years old) in the United States. The lifetime cost burden of all NASH patients in the United States was estimated to be enormous and expected to increase by approximately 400% in the next 5 years …”
Section: Economic Outcomes Assessmentsmentioning
confidence: 99%
“…On the other hand, aggressive lifestyle modifications that target components of metabolic syndrome could be beneficial. Patients with NASH at greatest risk for death can be identified based on the presence of metabolic conditions such as type 2 diabetes and significant fibrosis . Patients with significant fibrosis also have larger reductions in quality of life .…”
Section: Economic Outcomes Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation